Modern concepts of etiopathogenesis and approaches to the treatment of recurrent vulvovaginal candidiasis - Margarita R. Rakhmatulina (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Vulvovaginal candidiasis is a widespread infection caused by Candida. The disease affects 7580% of women of reproductive age at least once during their lifetime, and 920% of them indicate the presence of three or more episodes of the disease during the year, which is classified as recurrent vulvovaginal candidiasis (RVVC). To date, the question of the causes of the formation of recurrent forms of the disease has not been definitively resolved, since RVVC is also observed in women who do not have known risk factors. Due to the fact that about 2030% of patients with RVVC are healthy women without factors predisposing to its development, interindividual differences such as genetic predisposition and ethnicity, immune disorders, as well as the species diversity of Candida fungi and their antimycotic resistance may play a key role in the pathogenesis of idiopathic RVVC. In the literature review, the main etiopathogenetic mechanisms of the disease development are presented, the role of immune and genetic factors of predisposition to the development of recurrent vulvovaginal candidiasis is evaluated, changes in the species structure of the pathogen in recent years are analyzed. Modern approaches to the treatment of the disease are described, taking into account the indicators of antimycotic resistance, and the analysis of RVVC therapy regimens according to domestic and foreign clinical recommendations is carried out. The possibilities of using sertaconazole in the treatment of the disease are considered, the results of studies of its efficacy and safety in patients with vulvovaginal candidiasis are presented.